Spectroelectrochemical studies of electrochromic diarylethene ionic Liquids - Santiago, Sara (2022)
The authors are grateful for financial support from project PID2019-106171RB-I00 from the Ministerio de Ciencia e Innovación (MICINN) of Spain . ), Portuguese Foundation for Science and Technology/MCTES ( POCI-01-0145-FEDER-016387 and MIT-EXPL/CS/0055/2021 )). Finally, H.C. thanks financial suport in the scope of the framework contract foreseen in the numbers 4, 5, and 6 of article 23 of the Decree-Law 57/2016 of 29 August, changed by Law 57/2017 of 19 July. Publisher Copyright: © 2022 The Authors